Catheter ablation of atrial fibrillation and atrial flutter in patients with diabetes mellitus: Who benefits and who does not? Data from the German ablation registry. (1st July 2016) - Bogossian, Harilaos; Frommeyer, Gerrit; Brachmann, Johannes; Lewalter, Thorsten; Hoffmann, Ellen; Kuck, Karl Heinz; Andresen, Dietrich; Willems, Stephan; Spitzer, Stefan G.; Deneke, Thomas; Thomas, Dierk; Hochadel, Matthias; et al.
Abstract: Background: Diabetes mellitus (DM) is an independent risk factor for cardiovascular disease and arrhythmias. Procedural data and complication rates in patients with DM undergoing catheter ablation for atrial arrhythmias are unknown. Methods: The German Ablation Registry has been designed as a multi-center prospective registry. Between January 2007 and January 2010 data from ablation of right atrial flutter (AFlut) and atrial fibrillation (AF) were collected from 51 German centres. Patients with DM and without DM were compared. Results: We included 8175 patients who underwent catheter ablation of AFlut or AF. Patients with DM (n = 944) were older and presented significantly more severe comorbidities. Major periprocedural complications did not significantly differ between patients with and without DM for both ablation of AFlut and AF. Kaplan–Meier survival analysis for 366 days of follow-up, showed a significant increase of MACCE for DM patients as compared to controls after AFlut [6.1% vs. 3.4%(p = 0.002)], but not after AF ablation [1.2% vs. 0.9%(p = 0.59)]. Ablation of AFlut led to a comparable reduction of palpitations and NYHA class in both patient groups. AF ablation reduced palpitations and NYHA class in patients without DM, while patients with DM reported no improvement of NYHA class despite a reduction of palpitations. Conclusion: As compared to non-DM, patients with DM show no increased periprocedural risk and no increased arrhythmia recurrence after ablation of AFlut or AF. As expected patients with DM exhibit more comorbidities and an increased ongoing mortality after atrial flutter ablation presumably caused by the higher age of this group as compared to controls.